Modern views on teaching English in higher education - Gusak, Liudmyla; Malenitskyi, Denys (Південноукраїнський національний педагогічний університет імені К. Д. Ушинського, 2025)
This article explores innovative strategies for teaching the English language. The significance of this subject has notably increased in recent years, primarily due to advancements in technology that enable the implementation of unique and highly effective teaching methods. A key characteristic of these approaches is their adaptability. Today, there exists a multitude of effective English teaching techniques, in contrast to two decades ago when lessons were largely uniform and conventional. This adaptability is particularly crucial for Ukraine, which is fostering closer ties with more developed nations. Additionally, the Russian invasion of Ukraine has heightened the importance of English language acquisition, as millions of refugees have faced challenges in navigating new environments where communication with locals often necessitates proficiency in English or other languages.The subject matter is relatively novel and necessitates further exploration. Numerous studies and publications exist concerning inventive methodologies in the teaching of the English language. While these research efforts are thorough and detailed, it is crucial to present fresh insights. This article proposes various groundbreaking strategies within this domain.The data from the Razumkov Centre Sociological Service have been used in this article. These data have been analyzed to evaluate the command of English among Ukrainian citizens and highlight all problems and weak spots.This article presents a variety of effective strategies and techniques aimed at enhancing the educational experience, making it both engaging and productive. The central premise revolves around leveraging personal hobbies and interests to facilitate English language learning, which significantly boosts student motivation.Various approaches to this methodology are explored within the article, including some that are particularly innovative and unconventional, such as the ‘Artificial English Environment’ and ‘Virtual Theatre.’ However, it is important to note that not all methods will be suitable for every context. Educators must possess a deep understanding of their students to select the most appropriate techniques. The recommendations provided are grounded in our own observations and experiences, with many having demonstrated their practical effectiveness.
Keywords: English; innovative strategies; English language teaching; unconventional approaches; creativity; motivation; efficacy; creative teaching; 378.016:811.111